Distributed fiber optic sensors for measuring strains of concrete, steel, and textile reinforcement: Possible fields of application. (29th March 2022) - Zdanowicz, Katarzyna; Gebauer, Daniel; Koschemann, Marc; Speck, Kerstin; Steinbock, Oliver; Beckmann, Birgit; Marx, Steffen
Abstract: The article describes measurements of strains of concrete, steel and textile reinforcement with distributed fiber optic sensors (DFOS). The technology of distributed strain measurements gains currently increasing attention within the civil engineering field and indeed the DFOS can be applied in various measurement scenarios providing results and insights which were not possible before. Within this article, the fibers and adhesives that are most commonly used are compared and several measurement scenarios and their results are described, including precise strain measurements with high resolution as well as measurements on large‐scale specimens. Concrete strains were measured in a multiaxial compression stress state and also during setting and hardening and in flexural tests. Strains of the steel and textile reinforcement were monitored along the bond zone and also in flexural tests. Finally, cracking patterns were observed and compared with digital image correlation methods. Validated examples of applications of DFOS in laboratory work are described.